Pengaruh Ukuran Pemerintah Daerah, Umur Pemerintah Daerah, Status Pemerintah Daerah, Jumlah Penduduk, Jumlah SKPD, Belanja Pegawai dan Leverage Terhadap Kemandirian Keuangan Daerah - Inul Rofiq; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to determine the effect of the size of the local government, the age of the local government, the status of the local government, the total population, the total of SKPD, employee expenditure and leverage on regional financial independence. The population in this study is Regency/City in West Sumatra Province in 2015-2019. This study uses secondary data. The sampling technique used the Total Sampling method with a sample of 19 districts/cities with a period of 5 years. Data analysis used multiple linear regression analysis. The results of the study indicate that the status of local government, population and leverage affect regional financial independence. Meanwhile, the size of the local government, the age of the local government, the number of SKPD and employee expenditures have no effect on regional financial independence.